2001
DOI: 10.1136/bjsm.35.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis in students practicing sports: incidence of rubber sensitisation

Abstract: Background-Over the last few years, changes in cutaneous homoeostasis resulting from sports activities have been reported. In particular, alterations in sweating mechanisms, the hydrolipid barrier, and surface bacterial flora, together with exposure to atmospheric conditions and the need to use medicaments, detergents, and other topical substances, predispose subjects to allergic contact dermatitis. Objective-To evaluate the incidence of allergic contact dermatitis in a group of young people practising sports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
1
27
1
Order By: Relevance
“…One study of young fishermen presenting with ACD revealed an increased sensitivity to both nickel and mercaptobenzothiazole. 35 One case report noted that a graphite fishing rod caused unilateral palmar dermatitis in a fisherman after several hours of contact with the rod. 36 The fisherman's patch test was positive for IPPD.…”
Section: Snorkeling and Divingmentioning
confidence: 98%
See 2 more Smart Citations
“…One study of young fishermen presenting with ACD revealed an increased sensitivity to both nickel and mercaptobenzothiazole. 35 One case report noted that a graphite fishing rod caused unilateral palmar dermatitis in a fisherman after several hours of contact with the rod. 36 The fisherman's patch test was positive for IPPD.…”
Section: Snorkeling and Divingmentioning
confidence: 98%
“…33 The dermatitis may occur almost immediately or up to 48 hours after wearing the mask; N-isopropyl-N-phenylpara-phenylenediamine or IPPD, used as a rubber antioxidant, represent the most common sensitizing agents in mask burn. [33][34][35] FISHING Sports fishermen risk acquiring ACD most commonly on the hands from either the fishing rod or bait. One study of young fishermen presenting with ACD revealed an increased sensitivity to both nickel and mercaptobenzothiazole.…”
Section: Snorkeling and Divingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regarding IgE mediated allergies, rubber also represents a health threat. When being present in bound form, e.g., in scuba diving gear, latex allergens themselves or rubber processing additives may cause hypersensitivity contact dermatitis [13,23]. Since the 1980s, latex is increasingly used in gymnastic bands.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its physicomechanical properties, latex is an important material for sport equipment. Indeed, sporadically delayed type contact dermatitis was observed in students using latex sport equipment [13]. Only recently athletic trainers were advised of the possibility of immediate type allergic reactions upon latex exposure during exercise, and the usage of latex-free alternatives was suggested [14].…”
Section: Introductionmentioning
confidence: 99%